Membrane Proteomics Analysis of the Candida glabrata Response to 5-Flucytosine: Unveiling the Role and Regulation of the Drug Efflux Transporters CgFlr1 and CgFlr2 - Pais, Pedro; Pires, Carla; Costa, Catarina; Okamoto, Michiyo; Chibana, Hiroji; Teixeira, Miguel C. (Frontiers in Microbiology, 2016)
Resistance to 5-flucytosine (5-FC), used as an antifungal drug in combination therapy, compromises its therapeutic action. In this work, the response of the human pathogen Candida glabrata to 5-FC was evaluated at the membrane proteome level, using an iTRAQ-based approach. A total of 32 proteins were found to display significant expression changes in the membrane fraction of cells upon exposure to 5-FC, 50% of which under the control of CgPdr1, the major regulator of azole drug resistance. These proteins cluster into functional groups associated to cell wall assembly, lipid metabolism, amino acid/nucleotide metabolism, ribosome components and translation machinery, mitochondrial function, glucose metabolism and multidrug resistance transport. Given the obtained indications, the function of the drug:H+ antiporters CgFlr1 (ORF CAGL0H06017g) and CgFlr2 (ORF CAGL0H06039g) was evaluated. The expression of both proteins, localized to the plasma membrane, was found to confer flucytosine resistance. CgFlr2 further confers azole drug resistance. The deletion of CgFLR1 or CgFLR2 was seen to increase the intracellular accumulation of 5-FC, or 5-FC and clotrimazole, suggesting that these transporters play direct roles in drug extrusion. The expression of CgFLR1 and CgFLR2 was found to be controlled by the transcription factors CgPdr1 and CgYap1, major regulator of oxidative stress resistance.